EFL Students’ Perceptions to the Benefits of Online Group Discussion - Magfira, A.; Weda, Sukardi; Muhayyang, Maemuna (Har Press Indonesia, 2024)
This research aims to describe the students’ perceptions of online group discussion in EFL research methodology project. In frame of qualitative research, it utilized a case study research design taking 12 the Magister program students at Universitas Negeri Makassar. It used a semi-structured interview as the research instrument that was in thematic analysis coming with some steps, namely familiarizing self with the data, coding, generating and reviewing the themes, and writing the report. The results of this research showed that the students positively perceive the online group discussion in learning the course of Research Methodology indicated by (a) positive collaborative experiences, (b) increasing engagement, (c) challenging and stimulating, (d) social interaction, and (e) various learning styles. The positive collaborative experiences involve improving students’ understanding, share ideas and experiences, collaborative problems solving, collaboratively to finish the project; Increasing engagement allows an active participation; challenging and stimulating contributes to appreciate the challenge of defending the ideas, an opportunity to learning from the experience of others, learning from new viewpoints from group members, and to improve the quality of thinking and analysis; social interaction remains developing interpersonal communication skills, supportive learning environment, promotes effective teamwork, and improves learning experience; and various learning styles include platform for sharing ideas and experiences, variety of learning media and styles, improved students understanding. These findings lead to a conclusion that the use of the online group discussion in learning bridges the students to have a good interaction and communication among the students in EFL classroom.